2018
DOI: 10.1111/cas.13638
|View full text |Cite
|
Sign up to set email alerts
|

Loss of protein phosphatase 6 in mouse keratinocytes enhances K‐rasG12D‐driven tumor promotion

Abstract: Here, we address the function of protein phosphatase 6 (PP6) loss on K‐ras‐initiated tumorigenesis in keratinocytes. To do so, we developed tamoxifen‐inducible double mutant (K‐ras G12D‐expressing and Ppp6c‐deficient) mice in which K‐ras G12D expression is driven by the cytokeratin 14 (K14) promoter. Doubly‐mutant mice showed early onset tumor formation in lips, nipples, external genitalia, anus and palms, and had to be killed by 3 weeks after induction by tamoxifen, while comparably‐treated K‐ras G12D‐express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 27 publications
2
19
1
Order By: Relevance
“…Importantly, these targets are pre-existent and selected for during adjuvant treatment itself. While our sample size is sufficient for a robust gene discovery in advanced pancreatic cancer, we identified genes not commonly associated with the PDA landscape such as the nuclear exportin XPO1, the serine-threonine protein phosphatase PPP6C (24,31), or regulators of innate immunity (PRKCI, TRAF3) (34,35). These findings support the need for prospective and statistically robust efforts to sequence post-treatment PDA to better define the genes or pathways repeatedly targeted by somatic alteration.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Importantly, these targets are pre-existent and selected for during adjuvant treatment itself. While our sample size is sufficient for a robust gene discovery in advanced pancreatic cancer, we identified genes not commonly associated with the PDA landscape such as the nuclear exportin XPO1, the serine-threonine protein phosphatase PPP6C (24,31), or regulators of innate immunity (PRKCI, TRAF3) (34,35). These findings support the need for prospective and statistically robust efforts to sequence post-treatment PDA to better define the genes or pathways repeatedly targeted by somatic alteration.…”
Section: Discussionsupporting
confidence: 54%
“…By contrast, the genomic features of recurrent disease ( Fig. 2, Table S6) were notable for somatic alterations in additional genes, some of which are predicted to or likely to activate Mapk/Erk signaling (G12V mutation in KRAS, I679Dfs*21 mutation in NF1, R111X mutation in PPP6C) (23,24), PI3K/Akt/MTOR signaling (D323H hotspot mutation in AKT1, E542K hotspot mutation in PIK3CA, homozygous deletion of STK11) (25), or MYC/MAX regulated gene expression (Y1312X mutation in CHD8, W1004X mutation in MGA, X863_ splicing mutation in NOTCH1, up to 16-fold amplification of MYC) (26,27). Somatic alterations in genes predicted to affect chromatinmediated gene expression (up to 38-fold focal amplification of HIST1H3B, frameshift mutations in KMT2B, KMT2C, KMT2D, c.4471-1N>A splicing mutations in TRIP12) (28)(29)(30), nuclear export (E571K hotspot mutation in XPO1) (31) and DNA damage repair (c.497-1N>A splicing mutation in ATM, F134V mutation in TP53) were also found (32,33).…”
Section: Resultsmentioning
confidence: 99%
“…Our identification of PPP6C as a MEK phosphatase suggests that it also acts as a negative regulator of the core pathway driving melanoma, likely underlying at least in part its role as a tumor suppressor. Impaired dephosphorylation of MEK may also be relevant to previous studies showing that loss of PPP6C promotes oncogenic RAS-driven tumors in mouse keratinocytes ( Kurosawa et al, 2018 ) and in Drosophila ( Ma et al, 2017 ). PPP6C mutations in melanoma almost exclusively co-occur with BRAF and NRAS mutations, suggesting that alone they do not provide oncogenic levels of ERK signaling.…”
Section: Discussionmentioning
confidence: 64%
“…18 Recently, we observed that Ppp6c deficiency enhances K-ras G12D -dependent tumor promotion in keratinocytes. 19 These results indicate that, in these contexts, Ppp6c suppresses skin carcinogenesis. However, it remained unknown whether Ppp6c functioned similarly in the context of melanoma.…”
Section: Introductionmentioning
confidence: 83%